Numerical simulation of the ERICA tiltrotor using the HMB2 solver - Garcia, A.J.; Barakos, G.N. (My University, 2015)
Numerical simulations of the Enhanced Rotorcraft Innovative Concept Achievement tiltrotor have been performed using the Helicopter Multi-Block CFD solver. Comparisons with experimental data obtained in the German-Dutch Large Low-speed Facility and the S1MA wind tunnel are also presented. For this work, an aeroplane mode configuration, referred to as AC1, of the tiltrotor is considered. It is characterised by low speed and relatively high angle of attack of the aircraft. The Helicopter Multi-Block CFD method predicted the surface pressure coefficient at cross sections on the fuselage, nacelle, fixed wing, and tiltable wing of the tiltrotor accurately. Good overall agreement is obtained between CFD and wind tunnel data. In addition to fully resolved blades, computations with actuator disk models were also performed.
Keywords: Aerodynamics